Pharmacological treatment in pregnant women with moderate symptoms of coronavirus disease 2019 (COVID-19) pneumonia. (12th December 2022) - Nasrallah, Sebastian; Nguyen, Anh Q.; Hitchings, Laura; Wang, Jenny Q.; Hamade, Sara; Maxwell, G. Larry; Khoury, Alfred; Gomez, Luis M.
Abstract: Objective: Pregnant women with moderate symptoms of COVID-19 are at risk for progressing to severe or critical illness. While there are limited data on the management of severe COVID-19 during pregnancy, information on pharmacological treatments of moderate COVID-19 is lacking. We report clinical outcomes of pregnant women hospitalized due to moderate COVID-19 illness treated with a 5-day course of remdesivir, antibiotics, and/or glucocorticoids. Materials and methods: Case series of pregnant women hospitalized with moderate symptoms of COVID −19 pneumonia at two INOVA Health System hospitals from April 1 to December 31, 2020. Primary outcome was clinical recovery (breathing on ambient air and/or hospital discharge) on hospital day 7 (HD7). Cox regression analysis was performed to evaluate which variables were associated with the primary outcome. Results: Out of 748 pregnant women with confirmed infection by reverse transcriptase polymerase chain reaction, 35 were hospitalized due to moderate symptoms of COVID-19 pneumonia (median gestational age 29 weeks). There was no maternal death. Seventeen patients received remdesivir within 48 hours of hospitalization: 15 remained with moderate symptoms and 2 (who also received glucocorticoids) had progressed to critical COVID-19 at remdesivir initiation; all 17 women in this group achieved clinical recovery on HD7. Seven women received remdesivir >48 hours following admission after they began treatment with glucocorticoids ± antibiotics and worsened to severe or critical disease; they all required supplemental oxygen on HD7. Eleven women were treated with antibiotics ± glucocorticoids but no remdesivir; on HD7, 3/11 achieved clinical recovery. Clinical recovery was significantly different among treatment groups; p  < 0.001. When analyzing only women who remained with moderate symptoms at pharmacological treatments initiation, all 15 on remdesivir and only 3 of 11 on antibiotics achieved clinical recovery on HD7; p  < 0.001. Delaying remdesivir for >48 hours after admission (HR 2.32, 95% CI 1.45–4.16) and >4-day duration of symptoms prior to hospitalization (HR 1.65, 95% CI 1.27–3.50) had an inverse association with clinical recovery. Incidental oligohydramnios was seen in 3/24 (12.5%) of women within 5 days of completing remdesivir treatment. Elevated transaminases was prevalent in women treated with remdesivir (8/24, 33.3%). Conclusion: In our cohort, prompt initiation of remdesivir in pregnant women hospitalized with moderate symptoms of COVID-19 pneumonia within 48 hours of admission prevented worsening and allowed a fast clinical recovery by HD7. Deferring remdesivir for >48 hours after hospitalization and duration of symptoms >4 days before admission were independently associated with delayed clinical recovery and longer hospital admission. Ultrasound evaluation of the amniotic fluid in patients recovering from COVID-19 hospitalization should be considered.